2021
DOI: 10.1002/anie.202013962
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylic Acid Reductase Can Catalyze Ester Synthesis in Aqueous Environments

Abstract: Most of the well‐known enzymes catalyzing esterification require the minimization of water or activated substrates for activity. This work reports a new reaction catalyzed by carboxylic acid reductase (CAR), an enzyme known to transform a broad spectrum of carboxylic acids into aldehydes, with the use of ATP, Mg2+, and NADPH as co‐substrates. When NADPH was replaced by a nucleophilic alcohol, CAR from Mycobacterium marinum can catalyze esterification under aqueous conditions at room temperature. Addition of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…[294][295][296] A particularly noteworthy approach is the application of CAR for the synthesis of esters in water. 297 While up to now limited to primary alcohols, it shows that the catalytic machinery or several enzymes might be suitable for ester synthesis in water.…”
Section: Synthesis Of Esters and Amides In Watermentioning
confidence: 99%
“…[294][295][296] A particularly noteworthy approach is the application of CAR for the synthesis of esters in water. 297 While up to now limited to primary alcohols, it shows that the catalytic machinery or several enzymes might be suitable for ester synthesis in water.…”
Section: Synthesis Of Esters and Amides In Watermentioning
confidence: 99%
“…In addition to its use as starting precursors for hydroxylation, various PAs have just recently been shown to serve as substrates for a side activity of carboxylic acid reductase (CAR) from Mycobacterium marinum . CAR could be used to synthesize methyl cinnamate, methyl ferulate, methyl 4-hydroxyphenylacetate, and cinoxate (a commercial sunscreen ester formed from methoxycinnamic acid and 2-ethoxyethanol).…”
Section: Production Of Lignocellulosic Biomass-derived Productsmentioning
confidence: 99%
“…In addition to its use as starting precursors for hydroxylation, various PAs have just recently been shown to serve as substrates for a side activity of carboxylic acid reductase (CAR) from Mycobacterium marinum. 398 CAR could be used to synthesize methyl cinnamate, methyl ferulate, methyl 4hydroxyphenylacetate, and cinoxate (a commercial sunscreen ester formed from methoxycinnamic acid and 2-ethoxyethanol). Although yields of these compounds are rather low at this point, the esterification catalyzed by CAR can be conducted in aqueous environments, making the system attractive for future applications in metabolic engineering.…”
Section: Phenolic Acid-derived Productsmentioning
confidence: 99%
“…A recent study showed that CARs are also capable of ester formation. However, significant amounts of imidazole catalyst and alcohol nucleophile concentrations of over 1000‐fold excess were required to observe ester formation [20] …”
Section: Figurementioning
confidence: 99%